Enhanced oral absorption of 20(S)-protopanaxadiol by self-assembled liquid crystalline nanoparticles containing piperine: in vitro and in vivo studies - Jin, Xin (Dove Medical Press, 2013)
BACKGROUND: 20(S)-protopanaxadiol (PPD), similar to several other anticancer agents, has low oral absorption and is extensively metabolized. These factors limit the use of PPD for treatment of human diseases. METHODS: In this study, we used cubic nanoparticles containing piperine to improve the oral bioavailability of PPD and to enhance its absorption and inhibit its metabolism. Cubic nanoparticles loaded with PPD and piperine were prepared by fragmentation of glyceryl monoolein (GMO)/poloxamer 407 bulk cubic gel and verified using transmission electron microscopy and differential scanning calorimetry. We evaluated the in vitro release of PPD from these nanoparticles and its absorption across the Caco-2 cell monolayer model, and subsequently, we examined the bioavailability and metabolism of PPD and its nanoparticles in vivo. RESULTS: The in vitro release of PPD from these nanoparticles was less than 5% at 12 hours. PPD-cubosome and PPD-cubosome loaded with piperine (molar ratio PPD/piperine, 1:3) increased the apical to basolateral permeability values of PPD across the Caco-2 cell monolayer from 53% to 64%, respectively. In addition, the results of a pharmacokinetic study in rats showed that the relative bioavailabilities of PPD-cubosome [area under concentration–time curve (AUC)(0–∞)] and PPD-cubosome containing piperine (AUC(0–∞)) compared to that of raw PPD (AUC(0–∞)) were 166% and 248%, respectively. CONCLUSION: The increased bioavailability of PPD-cubosome loaded with piperine is due to an increase in absorption and inhibition of metabolism of PPD by cubic nanoparticles containing piperine rather than because of improved release of PPD. The cubic nanoparticles containing piperine may be a promising oral carrier for anticancer drugs with poor oral absorption and that undergo extensive metabolism by cytochrome P450.